2017
DOI: 10.1021/acs.iecr.7b03849
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Behavior of Blast Furnace Dust Particles during In-Flight Processes

Abstract: Blast furnace (BF) dust can be recycled as one of excellent secondary sources, in view of the valuable amounts of iron and carbon contents, and the in-flight reduction technology is considered to allow processing the fine metallurgical dusts efficiently. In this work, the reduction behavior of BF dust particles during in-flight process was studied using a high-temperature drop-tube furnace in laboratory scale. The effects of temperature and gas composition on the reduction degree were remarkable. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Xu et al. [6] applied the suspension reduction technology to recycle blast furnace dust. The XRD pattern showed that the dust mainly contained haematite, wustite, metallic iron and calcium ferrite.…”
Section: Iron Oxides Suspension Reduction Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al. [6] applied the suspension reduction technology to recycle blast furnace dust. The XRD pattern showed that the dust mainly contained haematite, wustite, metallic iron and calcium ferrite.…”
Section: Iron Oxides Suspension Reduction Kineticsmentioning
confidence: 99%
“…Moreover, researchers are developing other sustainable metallurgical processes based on high-temperature suspension reduction technologies as well. Xu et al [6,7] studied the reduction behaviour of blast furnace dust during the suspension reduction process to explore the possibility of this technology in treating solid wastes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has the advantage of maximizing the particle-to-plasma contact area, thus better leveraging the thermo-kinetic advantages offered by the plasma. Despite this advantage, the in-flight plasma reduction technique has received limited attention, with many of the studies using carbon as the reduction agent [28][29][30][31], rather than hydrogen. The major challenge is posed by the short residence times of a few tens of ms to a few seconds available for the reduction under typical conditions.…”
Section: Introductionmentioning
confidence: 99%